Relationship Between Recurrence of Chronic Subdural Hematoma with its Preoperative Volume - Saha, Kamalesh; Quader, Mahfujul; Karim, Md Rabiul; Sarkar, Tapas; Khan, Anisul Islam; Uddin, Md Kamal (Bangladesh Journal of Neurosurgery, 2022)
Background: Chronic subdural hematoma (CSDH) is commonly encountered in neurosurgical practice. However, surgical evacuation remains complicated by a high rate of recurrence. Objective: To assess the relationship between preoperative volume of chronic subdural hematoma and its post-operative recurrence. Methods: This hospital based prospective observational study was carried out in the Department of Neurosurgery, Chittagong Medical College Hospital (CMCH), Chattogram during April 2017 to October 2018. A total of 130 patients clinically and radiologically diagnosed with CSDH and underwent surgery were enrolled in the study. Patients were followed up for 6 months postoperatively to observe the recurrence rate by symptom evaluation and radiological investigation. Results: Mean age of the study population was 65.77 (±14.83) years with a range of 18-95 years where 81.5% were male. Among the patients, 51.5% (n=67) had history of trauma and 16.2% (n=21) used anti-coagulant. CT scan finding showed that 20.8% (n=27) had bilateral hematoma, 73.8% (n=96) had e”2 cm thickness of hematoma whereas 70.8% (n=92) had e”1 cm midline shifting. The mean pre-operative volume was 133.36 (±60.26) ml where 40.0% (n=52) had <115 ml and 60.0% (n=78) had e”115 ml of pre-operative volume. Recurrence of CSDH was observed in 10.8% (n=14) patients. Patients with bilateral hematoma collection, e”2 cm hematoma thickness , e” 115 ml pre operative volume and patients who used anti- coagulants significantly (p < 0.05) more recurrence of CSDH. There was a moderate correlation between pre operative CSDH volume and post operative recurrence , which was significant (rs = .598, p<0.001). Conclusion: There is a significant moderate correlation between pre operative CSDH volume and postoperative recurrence Bang. J Neurosurgery 2022; 11(2): 107-113